Day-to-day spontaneous social behaviours is quantitatively and qualitatively affected in a 16p11.2 deletion mouse model - Rusu, Anna; Chevalier, Claire; de Chaumont, Fabrice; Nalesso, Valérie; Brault, Véronique; Hérault, Yann; Ey, Elodie (Frontiers in Behavioral Neuroscience, 2023)
Background Autism spectrum disorders affect more than one percent of the population, impairing social communication and increasing stereotyped behaviours. A micro-deletion of the 16p11.2 BP4-BP5 chromosomic region has been identified in one percent of patients also displaying intellectual disabilities. In mouse models generated to understand the mechanisms of this deletion, learning and memory deficits were pervasive in most genetic backgrounds, while social communication deficits were only detected in some models. Methods To complement previous studies, we itemized the social deficits in the mouse model of 16p11.2 deletion on a hybrid C57BL/6NxC3H.Pde6b+ genetic background. We examined whether behavioural deficits were visible over long-term observation periods lasting several days and nights, to parallel everyday-life assessment of patients. We recorded the individual and social behaviours of mice carrying a heterozygous deletion of the homologous 16p11.2 chromosomic region (hereafter Del/+) and their wild-type littermates from both sexes over two or three consecutive nights during social interactions of familiar mixed-genotype quartets of males and of females, and of same-genotype unfamiliar female pairs. Results We observed that Del/+ mice of both sexes increased significantly their locomotor activity compared to wild-type littermates. In the social domain, Del/+ mice of both sexes displayed widespread deficits, even more so in males than in females in quartets of familiar individuals. In pairs, significant perturbations of the organisation of the social communication and behaviours appeared in Del/+ females. Discussion Altogether, this suggests that, over long recording periods, the phenotype of the 16p11.2 Del/+ mice was differently affected in the locomotor activity and the social domains and between the two sexes. These findings confirm the importance of testing models in long-term conditions to provide a comprehensive view of their phenotype that will refine the study of cellular and molecular mechanisms and complement pre-clinical targeted therapeutic trials.